Gastrectomy Versus Endoscopic Resection for Patients With Early-stage Gastric Adenocarcinoma: A Population-based Propensity Matching Study. Issue 10 (November 2020) - Yang, Jiahui; Ren, Mudan; Lu, Guifang; Liu, Huan; Liu, Chuan; Wang, Wancong; He, Shuixiang
Abstract : Background: This study aimed to compare the long-term results of patients who received these therapies. Materials and Methods: The Surveillance, Epidemiology, and End Results (SEER) database was queried in this research for data of patients with early gastric adenocarcinoma who underwent gastrectomy or endoscopic resection from 2007 to 2015. Propensity score matching was selected to generate a balanced cohort. Competing-risk regression analysis was carried out on the matched cohort. Cancer-specific mortality (CSM) and other cause-specific mortality (OCSM) were compared using adjusted subdistribution hazard ratios (SHRs). Results: In this study, 2214 patients with 191 underwent endoscopic treatment (ET) and 2023 who underwent surgery were identified. After propensity score matching, 474 patients were included in the analysis. The use of ET increased over time in patients, especially for those with cardia diseases. The ratio of 5-year CSM between ET and gastrectomy groups was 13.12% to 14.24% and the ratio of 5-year OCSM between them was 22.48% versus 14.31%. After adjusting for associated clinicopathologic factors, patients in both groups had similar CSM (SHR=0.87, 95% credible interval: 0.47-1.64, P =0.69) and OCSM (SHR=1.59, 95% credible interval: 0.94-2.68, P =0.08) in multivariable analysis. Conclusion: The long-term prognosis appears equivalent t in patients with endoscopic resection and gastrectomy.